Análise comparativa de políticas públicas e desenvolvimento regulatório da energia solar fotovoltaica no Brasil e na Alemanha - Marcus Filipe Vieira Soares (2019)
This master thesis proposes a comparative analysis of public policies and regulatory developments that support the implementation of photovoltaic solar energy in the Brazilian and German energy markets. Based on a bibliographic research carried out on relevant technical documentation (books, dissertations, theses, papers, journals, laws and normative resolutions), the work exposes the different perspectives about the theme, adopted by Brazil and Germany. Based on pre-defined criteria, and considering the specific aspects of each country, it sought to establish key points that show the different realities of the two countries, denoting that it is not just about applying the German success case in the Brazilian context. Cultural, historical, climatic and geographical differences prevent such models from being identical. In fact, they are not expected to be, because the specificities of each country determine what is best for each one. However, the study makes it possible to affirm that, with a well-defined law, as well as public policies adapted to the Brazilian reality, there is a promotion of important advances in the consolidation of photovoltaic solar energy in Brazil. This master thesis intends to contribute in this direction, from the identification, analysis and comparison of the evolution of the insertion, development and consolidation of photovoltaic solar energy in both countries.